The effect of grinding and/or airborne-particle abrasion on the bond strength between zirconia and veneering porcelain: a systematic review. Issue 1 (1st January 2017) - Lundberg, Karin; Wu, Lindsey; Papia, Evaggelia
Abstract: Objective: The aim of the study was to make an inventory of current literature on the bond strength between zirconia and veneering porcelain after surface treatment of zirconia by grinding with diamond bur and/or with airborne-particle abrasion. Material and methods: The literature search for the present review was made following recommended guidelines using acknowledged methodology on how to do a systematic review. The electronic databases PubMed, Cochrane Library, and Science Direct were used in the present study. Results: Twelve studies were selected. Test methods used in the original studies included shear bond strength (SBS) test, tensile bond strength test, and micro-tensile bond strength test. The majority of studies used SBS. Results showed a large variation within each surface treatment of zirconia, using different grain size, blasting time, and pressure. Conclusions: Airborne-particle abrasion might improve the bond strength and can therefore be considered a feasible surface treatment for zirconia that is to be bonded. Grinding has been recommended as a surface treatment for zirconia to improve the bond strength; however, this recommendation cannot be verified. A standardized test method and surface treatment are required to be able to compare the results from different studies and draw further conclusions.